Full exome sequencing of 11 families with Hidradenitis suppurativa. (3rd March 2021) - Theut Riis, P.; Loft, I.C.; Yazdanyar, S.; Kjærsgaard Andersen, R.; Pedersen, O.B.; Ring, H.C.; Huber, R.; Sultan, M.; Loesche, C.; Saunte, D.M.L.; Jemec, G.B.E.
Abstract: Background: Hidradenitis suppurativa (HS) is not a well‐studied or easily treated disease. Genetic information is essential for advances in the understanding and treatment of HS. This study aims to examine mutations in the gamma‐secretase complex, the Notch signalling pathway and to perform a Mendelian analysis of genetic variants that segregated with disease in a full exome sequencing of 11 families with HS. Method: Whole‐exome sequencing and Mendelian analysis of 11 families with HS from Denmark. Patients with a clinical diagnosis of active HS and a positive family history of HS were recruited. Consenting family members were enrolled and examined for HS as well. We included 11 families, with a total of 51 participants, 24 with HS and 27 without. Whole‐exome sequencing using HiSeq platform as paired‐end 2 × 150 bases was used. Results: We found mutations in the Notch pathway for all families. We found mutations in the PSENEN and APH1B of the gamma‐secretase genes. We also report 161 variants of unknown significance that segregated with the disease within these families. Conclusions: We did not find causative mutation for each family in this study, supporting the theory that HS is rarely caused by single‐gene mutations. We suggest that future genetic studies should be focused on genome‐wide association with thousands of cases, as this technique is better suited for suspected polygenic diseases.